Peta Distribusi Sebaran Kualitas Fisik Air Di Danau Sipin Kota Jambi Dan Rekomendasi Pemanfaatannya - Adrian Lutfi Raedjani; Muhammad Syarif; Mohd Zuhdi (Jurnal Pembangunan Berkelanjutan, 2022)
This study aims to determine the water quality in Lake Sipin based on the physical quality of the water, provide information on the distribution map of water quality based on the physical quality of the water and assess the management designation of Lake Sipin. Lake Sipin water is one of the sources of air used by the community for daily life. The quality of water in cultural activities is influenced by the life of the surrounding environment. Water quality has different quality standards for each designation, so it is important to monitor and evaluate water quality. The data collection technique was carried out by purposive sampling and using the Storet method and the Stepwise test was carried out. The parameters observed in this study were temperature, TDS, TSS, turbidity and pH. Results Based on the research, the quality standard results for each parameter are within the water quality standard. Calculations using the Storet method of water quality get a value of -4, meaning that the water quality of Lake Sipin is in a lightly polluted status. relationship between parameters that have a relationship from the results of the stepwise test. TSS and TDS have a relationship with the value of R = 0.661 with the assumption that if the TSS value increases, the TDS value decreases. Turbidity and TSS have a relationship with the value of R = 0.731 with the assumption that the greater the value of Turbidity, the greater the TSS value. pH and TDS have a relationship with the value of R = 0.518 with the assumption that the smaller the pH value, the greater the TDS value. The status of the water quality in Lake Sipin meets the water quality standards, meaning that the water quality in Lake Sipin is still good. The distribution map for water quality has a variety of distributions. The water in the Sipin lake can still be used according to the water class classification based on observations of air physics parameters.